Methodology and Baseline Data of a Comparative Exploratory Double-Blinded Randomized Study of Intravenous Iron on Fibroblast Growth Factor 23 and Phosphate in Chronic Kidney Disease - Xenophon Kassianides; Sunil Bhandari (Karger Publishers, 2023)
Modern intravenous iron compounds (e.g., ferric carboxymaltose [FCM] and ferric derisomaltose [FDI]) are utilized in the treatment of iron deficiency anemia in non-dialysis-dependent chronic kidney disease (ND-CKD). Product-specific alterations in the metabolism of fibroblast growth factor 23 (FGF-23) leading to hypophosphatemia have been described for certain intravenous iron compounds, such as FCM, with potential effects on bone and cardiovascular health and quality of life. No prior head-to-head comparison between FCM and FDI exists in ND-CKD. This single-center exploratory double-blind randomized controlled trial primarily aimed to investigate the differential impact of FCM and FDI on FGF-23 and phosphate in patients with iron deficiency +/− anemia and ND-CKD (stages 3a-5 - serum ferritin <200 μg/L or serum ferritin 200-299 μg/L and transferrin saturation <20%). Patients were randomized (1:1) to receive either FCM or FDI over two infusions (1 month apart). Follow-up was 3 months. Measurements of serum intact FGF-23, phosphate, vitamin D metabolites, parathyroid hormone, other bone metabolism, cardiovascular, and quality of life markers were monitored. 168 patients were prescreened. Thirty-five patients were screened; 26 patients were randomized. The mean (standard deviation) age was 67.9 (12.4) years and 17 participants were male. Most participants had stage 4 CKD (median [interquartile range] estimated glomerular filtration rate [eGFR]: 18.0 [11.3] mL/min/1.73 m2). A higher than normal median (interquartile range) level of intact FGF-23 (212.1 [116.4] pg/mL) was noted. Serum phosphate was within normal range, while parathyroid hormone was higher and 1,25 (OH)2 vitamin D lower than the normal range. The "Iron and Phosphaturia - ExplorIRON-CKD" trial will provide important information regarding the differential effect of intravenous iron products in terms of FGF-23, phosphate, and other markers of bone and cardiovascular metabolism, alongside patient-reported outcome measures in patients with ND-CKD.